The widower [videorecording (DVD)] - Shearsmith, Reece; Fleetwood, Kate, 1972-; Holmes, Federay (WGBY DVD Collection, 2015)
Based on a chilling true story, tells how a seemingly mild-mannered male nurse, Malcolm Webster, poisoned and murdered his first wife, attempted to do the same to his second wife, and further schemed to deceive his third fiancée.